Penyuluhan Cara Mendampingi Anak Belajar di Era Covid-19 - Nonci, Nurmi; Kamaruddin, Syamsu; Burchanuddin, Andi; Masdar, Muhammad (ADPERTISI, 2022)
During the Covid-19 pandemic, the role of parents inaccompanying children to learn has a high intensity. The role ofteachers in schools is returned to parents at home. This has animpact on the disruption of other schedules of housewives that theyare used to doing. This counseling aims to provide additional insightto housewives in Katimbang Village, Biringkanaya District,Makassar City in assisting their children in learning homes. Thiscounseling was attended by about 35 housewives with a duration of3 hours. This activity took place in the hall of the Kaimbang VillageOffice. The results of this counseling show that there is an increasein the insight of housewives after attending the counseling. There isno other way to deal with their complaints other than having to facethis reality and make social adaptations. The conclusion obtained isthat housewives must increase their insight in assisting children tostudy at home and take more parenting education both online andoffline.